Reconciling divergent findings on the speed of leverage adjustment - Khoo, Joye; Durand, Robert B.; Harris, Mark N. (2018)
Estimates of firms’ speeds of leverage adjustment (SOAs) vary wildly. Studies producing these estimates impose a strong constraint: An average SOAis estimated for all firms in a sample. Using finite mixture models (FMM) we uncover four distinct types of behaviors characterizing SOAs. The four behaviors in this regard can be classified as: Nearly stable (SOA= 2%); slower adjusters(SOA= 28%);faster adjusters(SOA= 62%) and drifters (SOA= -3%) who slowly move away from estimated leverage targets.